2023
DOI: 10.1038/s41598-023-38739-w
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new clinical syndrome: thoracic constriction without evidence of the typical funnel-shaped depression—the "invisible" pectus excavatum

Abstract: Pectus excavatum (PE) is a congenital malformation with a funnel-shaped depression of the sternum that can lead to cardiac symptoms. However, there are patients with thoracic constriction (defined as elevated Haller-Index > 3.25 determined by cardiac magnetic resonance imaging (CMR)) without visible evidence of PE, leading to similar complaints. Between January 2004 till June 2020, patients who underwent CMR for further evaluation of the heart, due to cardiac symptoms were enrolled and compared to controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…1). Twenty-five studies 22,24,34–56 totaling 2800 patients (mean age 27.9 ± 13.9 years, 48.2% females) affected by the most common TSA (PE, PC, scoliosis, SBS, and MS) were thus included in this systematic review. A summary of the included studies’ characteristics is reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Twenty-five studies 22,24,34–56 totaling 2800 patients (mean age 27.9 ± 13.9 years, 48.2% females) affected by the most common TSA (PE, PC, scoliosis, SBS, and MS) were thus included in this systematic review. A summary of the included studies’ characteristics is reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Another important limitation concerning studies conducted both before and after the year 2000 was the paucity of prospective data analyzing the clinical course of MVP individuals affected by TSA. Indeed, data concerning corrective surgery of TSA and/or prognostic evaluation of each study population was provided by seven studies 38,45,47,49,50,52,56 only.…”
Section: Limitations Of the Studiesmentioning
confidence: 99%